Unraveling the impact of institutional governance quality on non-performing loans in the CEMAC region - Kimal, Gam Dieudonne; Fonchamnyo, Dobdinga Cletus; Felix, Nkiendem (International Journal of Social and Administrative Sciences, 2025)
This study examines how the quality of institutional governance, specifically the control of corruption and the rule of law, influences non-performing loans (NPLs) in the CEMAC region. Using a secondary panel data set of the CEMAC countries from 2002 to 2022, the study employs panel data analysis and estimation techniques, including Panel Corrected Standard Error (PCSE), the Feasible Generalized Least Squares (FGLS), and the Driscoll-Kraay Standard Errors (DKSE), to overcome the challenge of cross-sectional dependence that exists in the panel data. The results reveal that the control of corruption has a highly significant negative impact on NPLs, meaning that improved control of corruption leads to a decrease in NPLs. In contrast, the rule of law does not exhibit a direct significant effect on non-performing loans, suggesting that while the rule of law remains an essential component of strong institutional governance, its direct influence on NPLs may not be as pronounced as that of corruption control. Based on these findings, the authors recommend that policymakers at the regional level within CEMAC should focus their efforts on implementing deep anti-corruption measures and fostering a culture of transparency and accountability to effectively curb the rise in non-performing loans.